Ferroptosis in glioma treatment: Current situation, prospects and drug applications - Zhou, Yuhang; Fang, Chaoyou; Xu, Houshi; Yuan, Ling; Liu, Yibo; Wang, Xiaoyu; Zhang, Anke; Shao, Anwen; Zhou, Danyang (Frontiers in Oncology, 2022)
Ferroptosis is a regulatory form of iron-dependent cell death caused by the accumulation of lipid-based reactive oxygen species (ROS) and differs from apoptosis, pyroptosis, and necrosis. Especially in neoplastic diseases, the susceptibility of tumor cells to ferroptosis affects prognosis and is associated with complex effects. Gliomas are the most common primary intracranial tumors, accounting for disease in 81% of patients with malignant brain tumors. An increasing number of studies have revealed the particular characteristics of iron metabolism in glioma cells. Therefore, agents that target a wide range of molecules involved in ferroptosis may regulate this process and enhance glioma treatment. Here, we review the underlying mechanisms of ferroptosis and summarize the potential therapeutic options for targeting ferroptosis in glioma.